Do the structures used by international hockey coaches for practising field-goal shooting reflect game centred learning within a representative learning design? - Slade, D. G.; Button, C.; Cochrane, D. (International Journal of Sports Science and Coaching, 2015)
The 1997 rule change in field hockey that removed the offside rule was, arguably, a watershed moment in the evolution of the game. Previous research sought to establish how this rule change had affected the way field-goals were being scored and coaches` philosophies towards practising that component of hockey. The Federation of International Hockey (FIH) 2011 Men`s Champions Trophy tournament provided an opportunity to revisit that research. Conclusions were that six of the seven team coaches observed at this tournament employed a game centred learning (GCL) design for practicing field-goal shooting (FGS) and these practices reflected a representative learning design (RLD). Video analysis of FGS supported the coaches` interpretations of the coupling of player perception and action processes in this skill. Overwhelmingly, but not totally, in the space of a little more than a decade, FGS practice, as observed by the author, had moved from drilling of skills in closed-skill contexts using command structures, to small-sided GCL practices reflective of a representative learning design. ABSTRACT FROM AUTHOR